2022
DOI: 10.1111/ene.15447
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric imaging and quantitative susceptibility mapping as complementary tools in the diagnosis of parkinsonisms

Abstract: Background and purpose: In the quest for in vivo diagnostic biomarkers to discriminate Parkinson's disease (PD) from progressive supranuclear palsy (PSP) and multiple system atrophy (MSA, mainly p phenotype), many advanced magnetic resonance imaging (MRI) techniques have been studied. Morphometric indices, such as the Magnetic Resonance Parkinsonism Index (MRPI), demonstrated high diagnostic value in the comparison between PD and PSP. The potential of quantitative susceptibility mapping (QSM) was hypothesized,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“… Pang et al (2022) [ 78 ] 3 T/32 SWI iPD: 77/MSA-P: 75 Iron accumulation of the dorsolateral PUT → more complex in MSA-P compared with iPD. Mazzucchi et al (2022) [ 79 ] 3 T/NR QSM PD: 31/MSA-c: 9/MSA-P:5/PSP: 24 ↑ χ of the PUT → Optimal diagnostic accuracy in PD/MSA-p comparison. ↑ χ of the PUT → Effective in distinguishing PD from PSP with good accuracy, though some overlap between the two groups exists.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Pang et al (2022) [ 78 ] 3 T/32 SWI iPD: 77/MSA-P: 75 Iron accumulation of the dorsolateral PUT → more complex in MSA-P compared with iPD. Mazzucchi et al (2022) [ 79 ] 3 T/NR QSM PD: 31/MSA-c: 9/MSA-P:5/PSP: 24 ↑ χ of the PUT → Optimal diagnostic accuracy in PD/MSA-p comparison. ↑ χ of the PUT → Effective in distinguishing PD from PSP with good accuracy, though some overlap between the two groups exists.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Ito et al (2017) [ 95 ] and Meijer et al (2015) [ 102 ] receiver operating characteristic (ROC) analysis showed a high accuracy of posterior PUT χ in differentiating PD from MSA-P groups. Mazzucchi et al's two studies using QSM and morphometric imaging in 2019 and 2022 demonstrated that an increased χ of the PUT was effective in distinguishing between PD, MSA, and MSA-P, with good diagnostic accuracy [ 79 , 93 ]. They also found that this method was successful in differentiating PD from PSP despite some overlap between the two groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the putamen, some studies indicated that the susceptibility of the red nucleus, substantia nigra, and globus pallidus could also be used to distinguish PSP from PD 15–17 . The latest study even showed that diagnostic accuracy comparing PD and PSP ranged from good (Putamen, Subthalamic nucleus) to optimal (red nucleus) 32 . However, there have been only a few related studies, which used different imaging techniques, so no unified conclusion can be drawn yet.…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 16 , 17 The latest study even showed that diagnostic accuracy comparing PD and PSP ranged from good (Putamen, Subthalamic nucleus) to optimal (red nucleus). 32 However, there have been only a few related studies, which used different imaging techniques, so no unified conclusion can be drawn yet.…”
Section: Discussionmentioning
confidence: 99%